A Systemic Lupus Erythematosus Accompanied with Myelodysplastic Syndrome, Grave’s Disease, and Sub-Acute Subdural Hemorrhage: A Case Report - I Nyoman Suarjana; Anggrada K. Utomo (Indonesian Rheumatology Association, 2022)
Background: The systemic lupus erythematosus (SLE) is a disease of autoimmune etiology affecting multiple systems, involving most commonly females of the reproductive age group and different clinical manifestations in each individual. Case presentation: A 23-year-old female patient with systemic lupus erythematosus (SLE) presented with myelodysplastic syndrome (MDS), Grave’s disease, and sub-acute subdural hemorrhage (SDH). She had chief complaints of severe headache and gum bleeding. Three weeks earlier, the patient experienced a head injury. SLE was diagnosed on biological and immunological clinical ACR criteria and the patient never had a therapy before. Bone marrow aspiration (BMA) test was performed with MDS result. Thyroid function test was performed with the result of decreased Thyroid Stimulating Hormone (TSH) and increased FT4 with diffused enlargement of thyroid gland. Brain CT Scan resulted in sub-acute SDH with midline shift of 1.13 cm to the left. The patient underwent subdural drainage with local anesthesia and received steroid, azathioprine, thiamazole and non- selective beta-blocker. She was hospitalized for 21 days and was discharged with good condition. Conclusion: Further investigation of the patient is needed to fully understand the correlation between MDS, Subdural Hemorrhage and Grave’s Disease in associated with SLE.